2015
DOI: 10.4103/0019-5049.149443
|View full text |Cite
|
Sign up to set email alerts
|

Role of wound instillation with bupivacaine through surgical drains for postoperative analgesia in modified radical mastectomy

Abstract: Background and Aims:Modified Radical Mastectomy (MRM) is the commonly used surgical procedure for operable breast cancer, which involves extensive tissue dissection. Therefore, wound instillation with local anaesthetic may provide better postoperative analgesia than infiltration along the line of incision. We hypothesised that instillation of bupivacaine through chest and axillary drains into the wound may provide postoperative analgesia.Methods:In this prospective randomised controlled study 60 patients aged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 22 publications
1
37
0
Order By: Relevance
“…The optimal dose of bupivacaine or ropivacaine for instillation during mastectomy is also inconclusive. Jonavithulla N. et al in their study concluded that a volume of 40 cc of local anaesthetic solution when instilled through two drains was associated with more complete spread of the drug and good pain relief postoperatively 10 On the other hand the studies using 20 cc volume of the drug showed ineffective pain relief after instillation through a single drain. 11 Hence in our study the drug volume of total 40cc was instilled through two surgical drains, one in the axilla and one in the chest wall, 20 cc each.…”
Section: Section: Anaesthesiologymentioning
confidence: 98%
“…The optimal dose of bupivacaine or ropivacaine for instillation during mastectomy is also inconclusive. Jonavithulla N. et al in their study concluded that a volume of 40 cc of local anaesthetic solution when instilled through two drains was associated with more complete spread of the drug and good pain relief postoperatively 10 On the other hand the studies using 20 cc volume of the drug showed ineffective pain relief after instillation through a single drain. 11 Hence in our study the drug volume of total 40cc was instilled through two surgical drains, one in the axilla and one in the chest wall, 20 cc each.…”
Section: Section: Anaesthesiologymentioning
confidence: 98%
“…The technique was simple and effective in reducing postoperative pain and no technique-related complications were found. 88 As regards the development of chronic postoperative pain, a qualitative systematic review that included 10 trials and 699 patients and a meta-analysis that analyzed 13 trials with 1150 patients confirm that continuous wound infiltration has an analgesic effect only in the first hours after surgery. 90,91 Similar results were shown by the multicenter study of Albi-Feldzer et al, who evaluated the efficacy in postoperative pain control, the incidence of chronic postoperative pain and its consequences on quality of life and mood comparing the efficacy of preoperative infiltration of the wound at second and third intercostal spaces and at the humeral insertion of major pectoralis with placebo in 236 patients.…”
Section: Breast Surgerymentioning
confidence: 99%
“…87 Even delivering LAs through the surgical drain may have some advantages. 88,89 Jonnavithula et al compared the instillation of 0.25% bupivacaine 40 mL (20 mL through each of the drain) with placebo. The drains were clamped for a period of 10 min after the drug administration.…”
Section: Breast Surgerymentioning
confidence: 99%
“…11 Topical application of local anesthetics or analgesic drugs into the mastectomy wound is a simple, yet effective technique that has been recently investigated. 12,13 It has been demonstrated that exogenous as well as endogenous opioid agonists have peripheral antinociceptive effects in inflamed tissues. 14,15 We hypothesized that the topical application of morphine/ bupivacaine combination would improve the quality of postoperative pain control, thereby decreasing the probability of developing chronic pain afterward.…”
mentioning
confidence: 99%